Área de Conservación Guanacaste, northwestern Costa Rica: Converting a tropical national park to conservation via biodevelopment. (20th January 2020) - Janzen, Daniel H.; Hallwachs, Winnie
Abstract: The 30, 000 hectare classical Costa Rican Parque Nacional Santa Rosa has used about 35 years and 107 million to be converted to the 169, 000 ha government‐NGO hybrid Área de Conservación Guanacaste (ACG). This semi‐decentralized conservation entity has today a staff of 150 paraprofessional resident Costa Ricans, biodeveloping at least 650, 000 multicellular species (Eucaryotes) into perpetuity for ACG survival through being integrated with its local, regional, national, and international society. ACG began in 1985 as an ongoing exercise of landscape‐level ecosystem rescue and restoration of a continuous swath from 6 km out in the Pacific ocean, across dry forested lowlands, up and over the volcanic Cordillera Guanacaste, and down into the rain‐forested Caribbean lowlands. It is being impacted by climate change, yet its diverse ecosystems hold hope for major biodiversity survival, albeit in new community assemblages. It quickly became simultaneously a biophysical challenge and an administratively novel challenge in decentralized conservation in a democratic tropical country. ACG specializes at being managed by on‐the‐job stimulated and trained residents with minimal formal education, searching for ways to involve ACG in its society without damaging its wildness, and pioneering ways to render wild biodiversity to being a welcome member at society's negotiating table. It continues to pay its bills through government subsidy, generous donors, payments for services, project grants, and huge in‐kind contributions from mutualisms. ACG hopes that the concept will spread south–south to other tropical countries while they still have some of their wild biodiversity with which to integrate. Abstract in Spanish is available with online material. Resumen: El clásico costarricense Parque Nacional Santa Rosa de 30, 000 hectares ha usado aproximadamente 35 años y 107 millones para convertirse al hibrido gobierno‐ONG Área de Conservación Guanacaste (ACG) de 169, 000 hectares. Este semi‐decentralizado entidad de la conservación tiene hoy día un equipo de 150 paraprofesional costarricense residentes, biodesarrollando por lo menos 650, 000 especies multicelulares (Eucaryota) hasta la perpetuidad para la sobrevivencia de ACG por medio de ser integrado con su sociedad local, regional, nacional y internacional. ACG empezó en 1985 como un ejercicio de rescate y restauración de un area continuo de 6 km mar Pacífico adentro hasta el bosque seco de tierra caliente, subiendo y pasando la Cordillera Guanacaste, y bajando al bosque lluvioso de tierra caliente lado Caribe. ACG esta siendo impactado por el cambio climático pero sus diversas ecosistémas contienen esperanza para sobrevivencia de grande escala para su biodiversidad, pero con una organización novedosa de las especies. ACG inmediata se convertió simultaneamente a estar un rompecabezas en biodiversidad y administración, especialmente en cuanto decentralización en un país democrática. ACG especializa en estar administrado por un equipo residente de poco educación formál, pero con ganas y aprendiendo por medio de su trabajo, buscando rutas para integrar ACG con su sociedad sin dañar su naturaleza salvaje, y siendo pionero en que la biodiversidad salvaje puede ser bien venido a las negociaciones en la sociedad. ACG siga pagando sus facturas por medio del presupuesto del gobierno, donadores generosos, pagos para servicios, becas para proyectos, y grandes pagos por medio de mutualismos. ACG espera que el concepto puede ampliarse sur‐sur a otros países tropicales mientras que todavía tienen biodiversidad silvestre con que pueden integrar.